New data on Linyphiidae spiders (Aranei) in the Maritime Province of Russia - Omelko Mikhail M; Marusik Yuri M. (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2025)
A survey of Linyphiidae in the Maritime Province revealed 28 species. Of them, one species is new for Russia, one for the Russian Far East, and nine for the Maritime Province. One species, Stemonyphantes mikhailovi sp.n. is described as a new to science. Nine poorly known species are illustrated. General appearance of 8 species is illustrated for the first time. Records of four species in the Maritime Province are the southernmost for their ranges.